2018
DOI: 10.2214/ajr.17.18660
|View full text |Cite
|
Sign up to set email alerts
|

Practical Suggestions on How to Move From Peer Review to Peer Learning

Abstract: The 2015 Institute of Medicine report on improving diagnosis emphasized that organizations and industries that embrace error as an opportunity to learn tend to outperform those that do not. To meet this charge, radiology must transition from a peer review to a peer learning approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Our research aims to demonstrate how the quality performance evaluation positively influences radiologists’ and technicians’ skills and affects the healthcare system in general. Due to the combination of technology, learning, and management, the authors have successfully achieved a “transition from a peer-review to a peer-learning approach” [ 3 ] in radiology.…”
Section: Discussionmentioning
confidence: 99%
“…Our research aims to demonstrate how the quality performance evaluation positively influences radiologists’ and technicians’ skills and affects the healthcare system in general. Due to the combination of technology, learning, and management, the authors have successfully achieved a “transition from a peer-review to a peer-learning approach” [ 3 ] in radiology.…”
Section: Discussionmentioning
confidence: 99%
“…by harnessing the power of group knowledge, when available (16). Textbooks, review articles, and increasingly searchable digital databases supplement diagnostic expertise when needed during image interpretation.…”
Section: Teaching Pointsmentioning
confidence: 99%
“…The report calls for health care professionals to develop a non-punitive culture that fosters identification of and learning from errors in diagnosis [1,2]. Many radiology practices are rising to this challenge by transitioning radiologist performance feedback from random audit-based peer review to continuous improvement and education-based peer learning [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite initial enthusiasm within the radiology community, peer review faltered in its ability to generate meaningful performance data; multiple studies have demonstrated the very low number of discrepancies and learning opportunities that peer review systems have identified [3,4,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation